PENGARUH MOTIVASI DAN KEBIASAAN BELAJAR SISWA TERHADAP HASIL BELAJAR MATEMATIKA - Rosyadi (Universitas Wiralodra, 2016)
This research aims to determine: (1) a positive influence of student’s motivation towards their mathematics learning outcomes; (2) a positive influence of student’s learning habits towards mathematics learning outcomes; (3) and a positive influence of the student’s between motivation and study habits combined toward mathematics learning outcomes. The research was conducted using a survey method explanation. In this research, there are three instruments. The instrument for the student’s mathematics learning outcomes is in essay form. While the instrument for student's motivation and study habits are in the form of questionnaires. Data analysis technique used in this research is simple regression and double regression. Based on the analysis, it can be concluded that: (1) there is a positive influence of the student's motivation towards their mathematics learning outcomes; (2) there is a positive influence of the student's study habits towards their learning outcomes; and (3) there is a positive influence motivation and study habits of students combined toward their outcomes in learning mathematics.